2007
DOI: 10.7182/prtr.17.1.a651683t34177n77
|View full text |Cite
|
Sign up to set email alerts
|

Stress among the family caregivers of liver transplant recipients

Abstract: Caregiving stress endures after transplantation. Professional intervention is needed to improve caregivers' quality of life and, consequently, that of transplant recipients as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 40 publications
2
23
1
Order By: Relevance
“…Hence, there is an urgent need for further studies and interventions directed at caregivers because there is evidence of stress among caregivers after liver transplantation. 19 Some limitations of this study should be noted. Because this is a cross-sectional study, it is necessary to reassess the participants in a longitudinal study in order to collect information about the indices of burden, stress, and depression at other stages of the treatment, including the stage after transplantation.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Hence, there is an urgent need for further studies and interventions directed at caregivers because there is evidence of stress among caregivers after liver transplantation. 19 Some limitations of this study should be noted. Because this is a cross-sectional study, it is necessary to reassess the participants in a longitudinal study in order to collect information about the indices of burden, stress, and depression at other stages of the treatment, including the stage after transplantation.…”
Section: Discussionmentioning
confidence: 89%
“…[17][18][19][20] Among the participants, both a lack of information and feelings of not being prepared were identified as stress factors. According to Caballero et al, 21 50% of the relatives of patients with chronic liver disease reported that they felt poorly informed about the disease and its complications, with up to 25% of the participants demonstrating a lack of knowledge of the relationship between the symptoms of the disease (including edema and encephalopathy) and feeding, intestinal transit, and alcohol consumption.…”
Section: Discussionmentioning
confidence: 99%
“…This can be coped with in different ways, from strategies facilitating adaptation to a new medical condition (for example, acceptance or positive reframing) to other strategies which would impede it. All this time, family members take on the role of caregivers, so they provide the patient with emotional support, take them to doctors’ appointments, look out for their dietary requirements, and do housework (Cohen et al, 2007). These caregivers may suffer from the frustration of their professional plans, employment complications, economic difficulties and even conflictive relations between the patients and their caregivers (Miyazaki et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Although liver transplantation lengthens the life of patients with chronic liver failure, as well as increases their quality of life, liver transplant recipients continue to experience health problems and symptoms after transplantation (Cohen et al. 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, family members are affected by the need to perform emotional and instrumental caregiving tasks, e.g. providing emotional support, accompanying the patient to medical appointments, attending to dietary requirements, and assuming extra roles and duties at home (Cohen et al. 2007).…”
Section: Introductionmentioning
confidence: 99%